Historical Judgement. - Gorman, Jonathan (Taylor and Francis, 2014)
The historical profession is not noted for examining its own methodologies. Indeed, most historians are averse to historical theory. In ""Historical Judgement"" Jonathan Gorman's response to this state of affairs is to argue that if we want to characterize a discipline, we need to look to persons who successfully occupy the role of being practitioners of that discipline. So to model historiography we must do so from the views of historians. Gorman begins by showing what it is to model a discipline by using recent philosophy of law and philosophy of science. There are different models at work,